Ali lahko napovemo čas vzdrževalnega zdravljenja z metadonom? - Iljaž, Rade (Zdravstveno varstvo, 2006)
Introduction: The Brežice Center for Prevention and Treatment of Illicit Drug Addiction (CPTIDA) was established in 1995 as part of the original network of such centres in Slovenia. The Brežice Centre employs a physician and a graduate nurse on a part-time basis. Methods: A retrospective study of the initial ten years of services provided in the Brežice Centre, and a comparisonof key indicators by age, gender and type of therapeutic intervention. The purpose of the study was to determine significant treatment predictors of tenure in methadone maintenance programme. Results: In the initial ten years of its existence, the Brežice Centre provided treatment to 205 Slovene citizens.Ninety-three of them, 68 men and 25 women, were included in the methadone maintenance programme, while others received psychological orpsychiatric interventions as aprt of the psychosocial programme. The averageage at first visit to the Centre was 21.8 years (1.9 years in psychosocial programme vs. 24 years in methadone maintenance programme). The one-way ANOVA revealed statistically significant differences in the average age of entrants to the psychosocial counselling programme depending on the type of illicit drug used (opiate, cannabis and benzodiazepines). The highest average dose and the highest initial dose of methadone were found to be statistically significant predictors of average tenure in methadone maintenance. Conclusion: The highest initial dose and the highest average doseof methadone are the factors to be considered when predicting methadone treatment tenure. The average age of programme entrants has no impact on the average tenure in methadone treatment.
Keywords: (RS)-methadones; Age Factors; droge; Drug Therapy; Metadon; Methadone; Psihoterapija; Psychotherapy; Sex Factors; Snov, zloraba, centri za zdravljenje; Spolni faktorji; Starostni faktorji; Substance Abuse Treatment Centers; Substance Dependence; vzdrževalno zdravljenje; zasvojenost